Who should bear the material responsibility for damage or destruction of immovable property during armed conflict? Lessons from Syria for Europe. - Spiesivtsev, Denys S. (Запорізький національний університет, 2021)
The article is devoted to consideration of the general problems of protection of property rights to real estates that were damaged or destructed during the armed conflict. It is defined that as of October 21, 2017, more than 10,000 buildings were damaged in Syrian city of Ar-Raqqa, and 3,326 were destroyed. Also in Aleppo were destroyed 4,733 buildings as well as 6,133 in Eastern Ghouta. The same damage was caused in other cities. This actualizes the question to who should bear the responsibility for such damage and what are the juridical mechanisms of its compensation? The author concludes that the situation in Syria clearly shows that internal armed conflict is associated with a high probability causing of property damage to the civilian population and legal entities. It is likely that recognition at the national level of the parties to the conflict, in addition to government forces, as violators in the manner established by the national law will lead to corresponding negative consequences for them. Particularly, person, who damaged or destroyed immovable property, is obliged to compensate appropriate damage as the offender. At the same time in the event that a state acts as an aggressor, individuals and entities whose real property has been damaged or destroyed during the conflict can claim compensation directly from such state (in case of use of national and international protection which characteristic of European countries) or to receive compensation from the state in respect of which an act of aggression has been committed. In its turn, defending state, with the help of reparations, may transfer to the aggressor all or a significant part of the damage that the population noted in the course of the conflict, even if such damage was caused by their own government troops in the course of the defense. But it important to admit that in second of mentioned situations there can be no juridical responsibility of defending state in cases when there is no causal relation between actions of such state and the damage. Thus in such situation the amount of compensation can be less than amount of the damage.
Keywords: immovable property; real estate; armed conflict; damage; destruction; compensation; 347.122:347.214.2(477)